Privilege, power, and difference - Johnson, Allan G. (New York, 2018)
Privilege, Power, and Difference is a groundbreaking tool for students and non-students alike to examine systems of privilege and difference in our society. Written in an accessible, conversational style, the 3rd edition links theory with engaging examples in ways that enable readers to see the underlying nature and consequences of privilege and their connection to it. This extraordinary book has been used across the country, both inside and outside the classroom, to shed light on issues of power and privilege. The thoroughly updated 3rd edition includes a new epilogue about the conflicting worldviews that can make these issues so difficult.
Keywords: Power (Social sciences)--United States